OPENWRT IN A VIRTUAL ENVIRONMENT USING VIRTUALBOX - FALKOVSKIY, IHOR; HOLOVNYA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is devoted to the creation of an OpenWRT virtual machine on the Oracle VirtualBox platform. OpenWRT is a Linux-based operating system specifically designed for embedded devices such as routers, offering advanced network configuration options and support for a variety of useful features. Existing work focuses on implementing OpenWRT in larger projects. However, deploying OpenWRT in virtualized environments may involve certain details that the researcher must work out before using OpenWRT to solve more practical problems in networking or other areas. The article provides a guide to installing Oracle VirtualBox, a free virtualization software that allows you to run multiple operating systems on a single computer. It covers important steps for setting up a virtual machine, including determining disk size, basic settings, and network settings. The main part of the article is devoted to the process of installing OpenWRT on a virtual machine. It describes where to download an OpenWRT image that contains an image of this operating system, methods for converting disk images to compatible VirtualBox formats. Advanced errors when converting disk images and their resolution are described. Also covered is setting up a virtual machine to install OpenWRT. The installation process is explained step by step. Attention is paid to solving the main existing difficulties during the installation process. The article is intended to help readers understand the process of creating an OpenWRT virtual machine on the Oracle VirtualBox platform and provides as many instructions as necessary to successfully install and configure OpenWRT on their computer. It is useful for researchers, students and anyone interested in installing and using OpenWRT in virtual environments. The publication of this article will help to understand the specifics of deploying OpenWRT in virtualized environments and to improve the understanding of its capabilities in practical situations.